Implications of WTO Agreements and Unilateral Trade Policy Reforms for Poverty in Bangladesh : Short versus Long-Run Impacts - Annabi, Nabil (World Bank, Washington, DC, 2012)
The authors examine the effects of WTO agreements and domestic trade policy reforms on production, welfare, and poverty in Bangladesh. They use a sequential dynamic computable general equilibrium (CGE) model, which takes into account accumulation effects, allowing for long-run analysis. The study is based on the 2000 Social Accounting Matrix (SAM) of Bangladesh including 15 production sectors, four factors of production (skilled and unskilled labor, agricultural and nonagricultural capital), and nine household groups (five in rural areas and four in urban areas). To examine the link between the macroeconomic effects and microeconomic effects in terms of poverty, the authors use the representative household approach with actual intra-group income distributions. The study presents five simulations for which the major findings are: (1) The Doha scenario has negative implications for the overall macroeconomy, household welfare, and poverty in Bangladesh. Terms of trade deteriorate and consumer prices, particularly food prices, increase more than nominal incomes, especially among poor households. (2) Free world trade has similar, but larger, impacts. (3) Domestic trade liberalization induces an expansion of agricultural and light manufacturing sectors, favorable changes in the domestic terms of trade. Although the short-run welfare and poverty impacts are negative, these turn positive in the long run when capital has adjusted through new investments. Rising unskilled wage rates make the poorest households the biggest winners in terms of welfare and poverty reduction. (4) Domestic liberalization effects far outweigh those of free world trade when these scenarios are combined. (5) Remittances constitute a powerful poverty-reducing tool given their greater importance in the income of the poor.